Membangun Daya Saing Lembaga Pendidikan Islam melalui Supervisi Kolaboratif dan Reflektif - Muhammad Iqbal Hatifuddin; Prim Masrokan Mutohar (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study examines the influence of educational supervision on teacher performance in enhancing the competitiveness of Islamic educational institutions. The research stems from the phenomenon of declining teaching quality and weak supervisory culture, which affect teacher professionalism and institutional competitiveness. The study aims to analyze the strategic role of educational supervision in improving teacher performance and strengthening the competitive advantage of Islamic educational institutions. This research employs a library research method by reviewing reputable journals, academic books, and relevant previous studies. Data were analyzed descriptively and analytically through literature synthesis. The findings indicate that educational supervision implemented collaboratively, reflectively, and based on Islamic spiritual values positively affects teachers’ motivation, professionalism, and integrity. Conceptually, this research contributes to the development of a spirituality-based educational supervision theory that bridges professional and religious aspects within Islamic educational management. The study concludes that effective supervision is not merely a monitoring tool but an integrative developmental mechanism that enhances teacher performance and sustainably strengthens the competitiveness of Islamic educational institutions.